Enriquecimiento de fincas cacaoteras con frutales y maderables en Alto Beni, Bolivia - Orozco, L.=700 1 Lopez, A.; Somarriba, E.
(Es, En)
ilus., 37 ref.
Keywords: AGROFORESTERIA; PLANTAS DE SOMBRA; CITRUS; HUERTOS FAMILIARES; PLANTACION EN LINEA; THEOBROMA CACAO; COSTA RICA